Synthesis of Benzofuran Derivatives through Cascade Radical Cyclization/Intermolecular Coupling of 2‐Azaallyls. (29th January 2019) - Deng, Guogang; Li, Minyan; Yu, Kaili; Liu, Chunxiang; Liu, Zhengfen; Duan, Shengzu; Chen, Wen; Yang, Xiaodong; Zhang, Hongbin; Walsh, Patrick J.
Abstract: Benzofurans are among the most popular structural units in bioactive natural products, however, the synthesis of such structures by radical cyclization cascade reactions is rare. Herein, we report a mild and broadly applicable method for the construction of complex benzofurylethylamine derivatives through a unique radical cyclization cascade mechanism. Single‐electron transfer (SET) from 2‐azaallyl anions to 2‐iodo aryl allenyl ethers initiates a radical cyclization that is followed by intermolecular radical–radical coupling. This expedient approach enables the synthesis of a range of polycyclic benzofurans that would otherwise be difficult to prepare. Abstract : Radikalische Maßnahmen : Eine milde und breit anwendbare Methode für den Aufbau komplexer Benzofurylethylamin‐Derivate verläuft über einen einzigartigen radikalischen Cyclisierungskaskaden‐Mechanismus. SET von 2‐Azaallyl‐ Anionen zu 2‐Iodarylallenylethern leitet eine radikalische Cyclisierung ein, auf die eine intermolekulare Radikal‐Radikal‐Kupplung folgt.